Environmental stress stability of microencapsules based on liposomes decorated with chitosan and sodium alginate. (1st April 2016) - Liu, Weilin; Liu, Wei; Ye, Aiqian; Peng, Shengfeng; Wei, Fuqiang; Liu, Chengmei; Han, Jianzhong
Highlights: Increase of polymer layers lead to monotonic changes in size, charge and morphology. pH induced more alteration of double-layered liposomes in appearance and size. High concentration of ion modified the structure but not the core of microencapsules. Polymers decoration efficiently prevent VC release from liposomes during digestion. Abstract: In this study, liposomes (LPs), chitosan (CH) coated LPs, sodium alginate (AL) and CH multilayered LPs (AL-CH-LPs) were developed based on the electrostatic interaction between charged polysaccharides at a certain pH. The increase of polymer layers on LPs led to a monotonic increase in size from ∼600 (LPs) to ∼1810 nm (AL-CH-LPs) and negative charge from −12.5 to −25.2 mV, regarded as a consequence of the formation of gradually expanded structures by cationic CH and anionic AL. The environmental stress including pH, storage and ionic strength (10–200 mM NaCl) had significant impact on the appearance and the particle size of the double-layered liposome (AL-CH-LPs). Furthermore, LPs showed the highest release rate of hydrophilic model ingredient (vitamin C) under gastrointestinal conditions, while the polymers had a capacity to reduce the vitamin C release in simulated intestinal fluid. This work provided useful information on the potential application of CH and AL based delivery systems.